2018
DOI: 10.1021/acs.jpcc.8b08398
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the First Nucleation and Growth Steps of Inorganic Solid Electrolyte Interphase Components

Abstract: The complexity of the solid electrolyte interphase (SEI) in lithium-ion batteries with graphitic electrodes has triggered extensive research efforts because of its crucial role on the lifetime of the battery. The SEI layer is composed of organic and inorganic species, resultant from the electrolyte decomposition at the electrode–electrolyte interface upon the first cycles of the battery. A stable SEI layer is essential to maintain the chemical and mechanical stability of the electrode as well as the electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Researchers in this field have made remarkable progress in describing electrolyte decompositions and SEI formations. Various experimental techniques have been applied to characterize the electrochemical and chemical responses of the SEI. ,,, Using computational approaches with quantum chemistry accuracy, “watching the SEI form” has been investigated by ab initio molecular dynamics (AIMD) , and density functional theory (DFT). , DFT compared to AIMD simulates a smaller system, limited largely to structural relaxation and no dynamics. However, it has significantly higher computational efficiency, thus allowing exploring a much larger variety of electrochemical and chemical feature spaces that are not accessible in AIMD.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in this field have made remarkable progress in describing electrolyte decompositions and SEI formations. Various experimental techniques have been applied to characterize the electrochemical and chemical responses of the SEI. ,,, Using computational approaches with quantum chemistry accuracy, “watching the SEI form” has been investigated by ab initio molecular dynamics (AIMD) , and density functional theory (DFT). , DFT compared to AIMD simulates a smaller system, limited largely to structural relaxation and no dynamics. However, it has significantly higher computational efficiency, thus allowing exploring a much larger variety of electrochemical and chemical feature spaces that are not accessible in AIMD.…”
Section: Introductionmentioning
confidence: 99%
“…96 Further computational results have also suggested that LiF clusters can form and then migrate to the surface and that this process depends on the surface termination of the electrode. 93 Cao et al also demonstrated with computation that existing LiF nuclei can result in accelerated PF 6…”
Section: Sins Of the Sei Layer On Si-based Anodesmentioning
confidence: 97%
“…Although the previous description looks conceptually simple, microscopic interpretations of several processes that would eventually lead to further improvements in cell performances still remain not fully understood. In addition to direct experimental efforts that are currently being undertaken to unveil such details, a series of recent quantum calculations and computer simulations with atomistic detail have provided valuable predictive information about equilibrium, stability, and dynamical characteristics associated with the redox processes taking place in the cells.…”
Section: Introductionmentioning
confidence: 99%